A Study of Improved Indoor Localization Accuracy using Looping Min-Max Technique - Thanadol Tiengthong; Thanadon Mankong; Nattapan Suwansukho; Phouthong Southisombath; Aditep Chaisang; Wiboon Promphanich; Sathaporn Promwong (My University, 2024)
This paper investigates the efficacy of WLAN technology at 5.8 GHz for indoor localization, a widely adopted and versatile approach due to its adaptability and ease of implementation. The choice of 5.8 GHz frequency offers several advantages, including reduced interference and higher data transmission rates, enhancing the precision and reliability of localization systems. Utilizing Received Signal Strength (RSS) for distance calculation is employed due to its computational simplicity and efficiency. The proposed methodology employs a modified Min-Max technique for estimating positions, iterating the Min-Max process until the distance error aligns with a predefined threshold. Comparative evaluation using Cumulative Distribution Function (CDF) demonstrates improved accuracy compared to conventional Min-Max methods. The research findings indicate promising enhancements in accuracy and efficacy for indoor localization using WLAN technology at 5.8 GHz. These advancements hold significant potential for real-time indoor localization applications, paving the way for improved indoor navigation and tracking systems in the future.
Keywords: Indoor and Outdoor Localization Technologies; Robotics and Sensor-Based Localization; Speech and Audio Processing